Microbial Contamination of Periorbital Tissues and Accessories of Children. Issue 6 (June 2016) - Cheung, Sin Wan; Boost, Maureen; Shi, Guang Sen; Cho, Pauline
ABSTRACT: Purpose: To investigate normal flora of children with and without orthokeratology (ortho-k) treatment, and the associations between carriage of Staphylococcus aureus and Gram-negative rods with contamination of contact lenses and lens cases in ortho-k subjects and with spectacles of control subjects. Methods: Twenty-three ortho-k subjects (treatment >12 months) and 20 control myopic subjects aged 7–14 years were recruited. Samples were collected from four sites surrounding the left eye (lower conjunctiva, upper and lower eyelids, and eyelashes) for all subjects, spectacles for control subjects and contact lens accessories for ortho-k subjects. Samples were cultured, total numbers enumerated, and isolates identified using chromogenic agars. Results: Ortho-k subjects had significantly less total isolates in the conjunctiva than controls (p = 0.009). Otherwise, carriage rates in normal flora levels of the peri-orbital tissues were not significantly different between the two groups (p > 0.19). The total isolates and carriage rates of normal flora on spectacles, contact lenses, and lens cases were similar to those identified on the skin tissues. Small numbers of bacteria were identified from the multipurpose solution of two ortho-k subjects. Although the association between the carriage of S. aureus with contamination of accessories was statistically significant only in control subjects (p = 0.03), ortho-k subjects not yielding S. aureus and Gram-negative rods from samples of their peri-orbital tissues tended to be less likely to have these organisms in their accessories. No Pseudomonas was isolated from any of the sites sampled and no Acinetobacter was isolated from any of the accessories. Conclusions: Ortho-k may lower the total number of bacteria in conjunctiva due to the use of solution and lenses, but the physiologic effect of this treatment on the types of normal flora in children was minimal and should not increase the risk of microbial keratitis in children with good compliance.